2013
DOI: 10.1111/febs.12620
|View full text |Cite
|
Sign up to set email alerts
|

SNAP‐23 and VAMP‐3 contribute to the release of IL‐6 and TNFα from a human synovial sarcoma cell line

Abstract: Fibroblast-like synoviocytes are important mediators of inflammatory joint damage in arthritis through the release of cytokines, but it is unknown whether their exocytosis from these particular cells is SNARE-dependent. Here, the complement of soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) in human synovial sarcoma cells (SW982) was examined with respect to the secretion of interleukin-6 (IL-6) and tumour necrosis factor a (TNFa), before and after knockdown of a synaptosome-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…Indeed, our data show that siRNA knockdown of VAMP3 impairs IL-6 secretion by monocyte-derived dendritic cells as previously observed for RAW264.7 murine macrophages (Manderson et al, 2007) and SW982 human synovial sarcoma cells (Boddul et al, 2014). As supported by our FRET-FLIM data the increased complexing of VAMP3 with Stx4 is thus likely responsible for the increased secretion of IL-6 and other cytokines by activated dendritic cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, our data show that siRNA knockdown of VAMP3 impairs IL-6 secretion by monocyte-derived dendritic cells as previously observed for RAW264.7 murine macrophages (Manderson et al, 2007) and SW982 human synovial sarcoma cells (Boddul et al, 2014). As supported by our FRET-FLIM data the increased complexing of VAMP3 with Stx4 is thus likely responsible for the increased secretion of IL-6 and other cytokines by activated dendritic cells.…”
Section: Discussionsupporting
confidence: 87%
“…Because of the photobleaching we were unable to measure FLIM of the same cell pre- and post-LPS treatment. VAMP3 is known to mediate release of inflammatory cytokines by the murine macrophage cell line RAW264.7 (Manderson et al, 2007) and the human synovial sarcoma cell line SW982 (Boddul et al, 2014). VAMP3 is also required for the secretion of cytokines by LPS activated monocyte-derived dendritic cells, as siRNA knockdown of this SNARE impaired release of the cytokine IL-6, as shown by ELISA (Figure 5C–D; Figure 5—figure supplement 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the limited imaging depth of TIRF microscopy, we could only measure exocytic events at the ventral membrane and not at the dorsal membrane. We recently showed that a post-fusion complex of the SNARE VAMP3 (responsible for IL-6 release [3,6,23]) is present at the dorsal membrane of dendritic cells, suggesting that exocytosis does take place at this side [3]. This is in line with findings in macrophages where no evidence was found for polarized secretion of IL-6, whereas tumor necrosis factor a (TNFa) was secreted predominantly at the phagocytic cup [6].…”
Section: Resultssupporting
confidence: 79%
“…The lower estimate is assuming completely nonpolarized secretion, as suggested by a macrophage study where there was no evidence found for polarized secretion of IL‐6 in macrophages, whereas TNFα was predominantly secreted at the nascent cup of phagosomes . The higher estimate is for the case that IL‐6 is exclusively released at the ventral membrane, which we consider unlikely given that we recently showed the presence of VAMP3 in postfusion cis ‐SNARE complexes (i.e., the SNARE for IL‐6 release ) at the dorsal membrane. In the case where release of IL‐6 would be higher at the dorsal than the ventral membranes, we underestimate the rate of exocytic events and the average number of IL‐6 molecules per vesicle will be even lower.…”
Section: Discussionmentioning
confidence: 84%
“…VAMP3 and SNAP-23 contribute to IL-6 and TNF secretion stimulated by IL-1b (61), and recent evidence supports the idea that VAMP3 mediates the secretion of components specifically from the recycling endosomes (62). In macrophages, for example, VAMP3 was found to be a marker of recycling endosomes and was involved in LPS-induced TNF secretion (63).…”
Section: Discussionmentioning
confidence: 73%